PERSEPSI GURU TERHADAP IMPLEMENTASI KOMPETENSI MANAJERIAL KEPALA SEKOLAH DI SMP NEGERI SE KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Afiful Fuadi (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about the theacher’s perception toward implementation of managerial competency of headmasters. The population is 169 teacher’s and the sample is 43 people that taken by simply random sampling. The instrument of this research is question with Likert scale models  that had tested for validity and reliability. Data analyzed using mean score. The result of this research are the teachers perception about implementation managerial competency of headmasters in SMP Negeri Kecamatan Pasaman Kabupaten Pasaman Barat stay in good category. Key word : managerial competency of headmasters